Regional features of gastroduodenal disease, associated with Helicobacter pylori infection, in the North Ossetia - E. A. Kornienko; F. V. Bazrova (Журнал инфектологии)
The aim of this study was to evaluate the structure of gastroduodenal disorders, virulent feathers of Helicobacter pylori (HP) strains and efficacy of eradication therapy in children of the North Ossetia (Alania). 1265 children from 4 till 18 years old were examined, НР was found in 84%. 53% of HP(+) atients had erosions and ulcers of the stomach and duodenum. Strains, resistant to clarithromycin, were revealed in 13% of the patients. We have estimated efficacy of 4 regimes of eradication therapy. Regimes, that included clarithromycin and metronidazole, had the lowest efficacy the worst compliance. The best results were observed in triple therapy, including PPI, amoxicillin and bismuth, and quadrotherapy with PPI amoxicillin, bismuth and nifuratel. The duration of therapy should not be shorter than 10 days.